ASSESSMENT OF CRITICAL THINKING SKILLS AMONG THE UBLC COLLEGE STUDENTS AND TEACHERS - Abigail Marie Umali-Hernandez, R.N., M.A.N.; Alphie G. Garing, MALT; Minerva Apita-Chavez, Ph. D, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Critical thinking is considered as a factor in the quality of education that the local can offer. Thus, the study aims to identify the perception of the teachers and students in infusing critical thinking skills in terms of classroom instruction. This study also explores how teachers perceive their teaching of critical thinking skills and their students’ perceptions about their understandings and awareness of learning critical thinking. Moreover, this propose intervention activities to develop critical thinking skills among college students. The questionnaire from the Foundation for Critical Thinking was administered to 1,050 respondents from the teachers and students. Results show the strength of the students in terms of critical thinking would be their view on determining the reliability of the sources of the information they use and receive in class. There is a need to improve the teachers’ instruction to aid the students in identifying the differences among assumptions, inferences, and predictions so they can perform their assigned task properly.